Developing the Professional Self-Concept: Role Model Construals in Early, Middle, and Late Career Stages - Gibson, Donald E. (Organization Science, 2003)
While previous literature tends to focus on role models as significant other people, particularly in one's early life, this study finds that individuals tend to construe their role models as a selection process of attributes from others throughout their career. I discovered that individuals primarily construe their role models along positive/negative, global/specific, close/distant, and hierarchically superior/peer-subordinate dimensions, and that across the career span, the tendency to observe role models did not change. Rather, the emphasis placed on different dimensions of role models changes. Early-stage respondents who are working on creating a viable self-concept were more likely to construe their role models as positive, close, and sources of a range of attributes. Middle- and late-stage respondents were more likely to see their role models as sources of specific, and often negative, attributes. The study suggests that these observed patterns are related to individuals' increasing confidence in their professional self-concept. In early stages, individuals pay attention to role models to create a viable self-concept; in middle stages, they seek to refine their self-concept, and in late stages, they seek to enhance and affirm their self-concept.